1996
DOI: 10.1111/j.1365-3040.1996.tb00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable patterns of antioxidant protection but similar ethene emission differences in several ozone‐sensitive and ozone‐tolerant plant selections

Abstract: Six pairs of O3‐sensitive and O3‐tolerant cultivars, clones or populations of different plants (tobacco, plantain, clover, radish, poplar and loblolly pine) were taken through identical but short episodic exposures to O3 in a controlled‐environment fumigation system. Emissions of ethene and concentrations of polyamines, total phenols and ascorbate as well as levels of reduced glutathione and ascorbate in fumigated and clean air controls were determined in these various cultivars, clones and populations. A larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 26 publications
4
41
0
2
Order By: Relevance
“…This role of ethylene has been elaborated in two tobacco cultivars of differential ozone sensitivity (Langebartels et al, 1991) and recently in several ozonetolerant and -sensitive plant selections (Wellburn and Wellburn, 1996). It was found that ethylene emission was the only consistent parameter in all systems showing significant increases in sensitive plants and no changes or even reduction below that of controls in ozone-tolerant selections (Wellburn and Wellburn, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This role of ethylene has been elaborated in two tobacco cultivars of differential ozone sensitivity (Langebartels et al, 1991) and recently in several ozonetolerant and -sensitive plant selections (Wellburn and Wellburn, 1996). It was found that ethylene emission was the only consistent parameter in all systems showing significant increases in sensitive plants and no changes or even reduction below that of controls in ozone-tolerant selections (Wellburn and Wellburn, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Senescence is a complex and highly regulated process that mobilizes the nutrient components to other parts of the plant, and is usually considered to be a specialized form of PCD (Quirino et al 2000). Ethylene is widely known to modulate organ senescence induced by various stress factors such as plant pathogens (Moore et al 2000), O 3 (Wellburn and Wellburn 1996;Pell et al 1997) and hypoxia (He et al 1996). Since O 3 exposure induces ethylene and causes several morphological and physiological changes often associated with senescence, Pell et al (1997) have suggested that O 3 exposure reduces plant productivity by activating a slow cell death process referred to as``premature senescence.''…”
Section: Ethylene Signaling: Senescence or Hr-like Cell Deathmentioning
confidence: 99%
“…Air pollution has been correlated with elevated polyamine levels in plants as well. Plants respond to pollutants such as ozone and SO 2 by producing high levels of polyamines (Priebe et al, 1978;Kramer et al, 1991;Wellburn and Wellburn, 1996). In all these studies, polyamine concentrations in plant tissues increase from high micromolar (under normal conditions) to millimolar range upon stress treatments.…”
mentioning
confidence: 98%